Evaluation of carbon-reduction through integration of vertical and horizontal landscape design for hotel premises - Othman, Rashidi; Abu Kasim, Siti Zubaidah; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim (IWA PUBLISHING, 2017)
The excessive reliance of fossil fuels and carbon production from daily appliances especially in tourism accommodation premises could cause detrimental impact to the surrounding environment. This is due to the increase of carbon emissions which is one of the major contributors for greenhouse effect especially in urban areas. In order to alleviate the carbon footprint by those premises, one of the promising methods to reduce carbon dioxide emission to the atmosphere is by selecting an appropriate plant species as well as optimization of spatial organization of plant materials. Besides character of the plant materials, criteria such as locality, age, diameter and height are very much influenced the carbon sequestration rate. This study established that even with limited green space areas for tourism accommodation premises such as hotel, the carbon sequestration rate can be further increased with the right selection of plants, at the right place with the right design. Therefore this study aimed to monitor, calculate and predict how much carbon can be absorbed by proposed plant species at certain period of time. The significance outcomes of this study will be green approach to monitor and sequester carbon toxicity using plant species also a novel landscape design approach to neutralize carbon emission which is cost effective and environmental friendly.